The conflict element in the both heroic poems: Nizami’s (Khasraw u shirin ) and Khani’s (Mamu Zin) - Jihad Rashid (پژوهشنامه ادبیات کردی, 2019)
Nizami is one of the masters of epics, who was difficult to find a rival for in the Persian literature, He was a leader for a lot of researchers and writers. Nizami’s ability in writing this heroic poem made most of the sensitive Persian and non-Persian poets to be affected by him either by imitating him or deriving him. This influence has been derived to the Kurdish Literature in a very attractive way and since Conflict is one of the important effective elements of the heroic poem, for that the researcher of this research puts the light on this element in both epics: Nizami’s (khasraw u Shirin) and Khani’s (Mam u Zin). The result of this research concludes that conflict in these previous epics was the relying element in developing the plot, and by using the analytical-descriptive method the researcher will show: the origin of writing modern epics, the role of conflict in the heroic poems of (Khasraw u Shirin) and (Mam u Zin), and it will evaluate the kinds of conflict in a way it will be explicit to the reader.